Environmental education during the COVID-19 pandemic: lessons from Ontario, Canada - Millward, Andrew A.; Borisenoka, Inga; Bhagat, Nickesh; LeBreton, Gregory T. O. (Frontiers in Education, 2024)
This study investigates the integration of place-based environmental education (PBEE) during emergency remote education (ERE) and in-person teaching, considering the implications of COVID-19. The objectives include (a) to understand if and how teachers used PBEE as a pedagogical learning tool during ERE, (b) to identify PBEE adaptations for implementation in an online context, and (c) to explore opportunities and barriers to PBEE during ERE. Ontario (Canada) educators’ perspectives were obtained through an online survey and focus groups. Using non-parametric statistical analyses, perspectives concerning opportunities and challenges to integrating and delivering PBEE in lessons were identified. Additional focus included educators’ views on student receptivity and knowledge retention. Findings indicate educators’ appreciation for PBEE as a pedagogical approach, yet delivery challenges arise from systemic barriers causing inconsistency in PBEE delivery. Obstacles include curriculum demands, institutional disinvestment, grade-level constraints, and limited training. Despite challenges, educators showcase innovation and commitment to PBEE during ERE, emphasizing its enduring value. The study underscores educators’ resourcefulness in adapting PBEE methods and the potential for renewed significance of outdoor education amidst the pandemic’s influence on students’ connection to nature.